Maternal mortality: The role of Mycoplasma hominis and its impact on neonatal health - Vivian Osei Poku (Health Sciences Review, 2022)
Maternal mortality remains a public health challenge. Every day, approximately 800 women die worldwide from causes related to pregnancy and childbirth that can be prevented. Maternal mortality continues to be prevalent in developed countries and developing countries with infections being one of the major causes of this canker, these include genital mycoplasma infections. Mycoplasma hominis (M. hominis) is a facultative human pathogen that is mostly detected in the lower urogenital tract in sexually active healthy men and women. It is known to have adverse effects on the outcome of pregnancy. M. hominis has been identified in women from family planning and prenatal clinics much more frequently and it has been associated with pyelonephritis, pelvic inflammatory disease, postpartum septicemia, endometritis, and preterm birth. M. hominis also affects neonatal health leading to respiratory distress, neonatal meningitis, and congenital pneumonia. This review provides an overview of the current knowledge on Mycoplasma hominis, the dangers it poses to maternal and neonatal health, and its detection and treatment.